Earnings management and Stock Market Return: An Investigation of Lean against the Wind Hypothesis - Khan, Amir Sajjad (School of Business and Management Institut Teknologi Bandung, 2013)
This study attempts to investigate the â€œlean against the wind hypothesisâ€. For this purpose the relationship of earnings management to that of the aggregate stock market return was investigated. Data for the year 2005 to 2009 was examined and Panel Data techniques were applied on the data set. F-statistics were used to check for appropriateness of the model, Housman test were used to finally decide for fixed effect model. Results of the paper were against the existence of lean against the wind behavior of the firms towards the aggregate under valuation of stock market returns. These Results were in favor of the past study of Cohen and Zarowin (2011).Keywords: Earnings management, Discretionary accruals, Modified Jones model, KSE